CPP302/CSE401 - Artificial Intelligence April 1999 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1999)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 1998/99 February 1999 CPP302/CSE401 • Artificial Intelligence Duration: [3 hours] INSTRUCTION TO CANDIDATE: • Please ensure that this examination paper contains SIX questions in SEVEN printed pages before you start the examination. • Attempt ALL questions. • You are required to return back the question paper. • If you choose to answer the questions in English. at least one question must be answered in Bahasa Malaysia.